Self-assembled multi-structured reduced graphene oxide/zinc composite - Teixeira, Jean Valdir Uchôa [UNESP]; Mastelaro, Valmor Roberto; Lisboa-Filho, Paulo Noronha [UNESP] (Springer Nature, 2024)
Graphene-based materials have presented significant attention owing to their intriguing properties and the potential for the production of diverse composite formulations. Among these avenues, the incorporation of dopamine as an anchoring agent stands out, fostering the emergence of multiple phases at the graphene surface. In this study, we propose a straightforward methodology for the fabrication of reduced graphene oxide/zinc composites, leveraging dopamine molecules as intermediaries, facilitated by UV-C irradiation. The outcomes vividly underscore the adeptness of dopamine in mediating the attachment of zinc hydroxide and zinc hydroxide nitrate hydrate onto the core-reduced graphene oxide (RGO). These interactions engender the retention of RGO’s structural–functional groups, a reduction in interplanar spacing, and the establishment of a mesoporous framework characterized by pore diameters surpassing 200 Å. Collectively, the results firmly establish the successful synthesis of RGO/Zn composites, positioning them as promising candidates for diverse applications by capitalizing on the inherent attributes of graphene-based materials and the laminar architecture of zinc hydroxide.
Keywords: Characterization; Composite; Mesoporous structure; Nanostructures; Reduced graphene oxide